Familial Mediterranean Fever in Chinese Children: A Case Series - Li, Ji; Wang, Wei; Zhong, Linqing; Pan, Junyan; Yu, Zhongxun; Jian, Shan; Wang, Changyan; Ma, Mingsheng; Tang, Xiaoyan; Wang, Lin; Quan, Meiying; Zhang, Yu; et al. (Frontiers in Pediatrics, 2019)
Background: Familial Mediterranean fever (FMF) is an inherited auto-inflammatory disorder and is extremely rare in Chinese. This study aimed to investigate the demographic, clinical, and genetic features of FMF in a series of Chinese pediatric patients. Methods: This was a retrospective case series of children with recurrent febrile or inflammatory episodes and referred to the Peking Union Medical College Hospital between 06/2013 and 06/2018. All suspected patients were genetically diagnosed and met the Tel-Hashomer criteria for FMF. Demographic, clinical, genetic, and treatment characteristics were collected. Descriptive statistics were used. Results: Eleven patients were included (seven boys and four girls). The median age at the time of disease onset was 7.1 (range, 3–12) years, while the median age at diagnosis was 10.9 (range, 6–15) years. The median delay in diagnosis was 2.1 years (range, 6 months to 6.7 years). Fever (100%, 11/11) was the most common symptom, followed by joint pain (63.6%, 7/11), rash (54.5%, 6/11), abdominal pain (36.4%, 4/11), and oral ulcers (18.2%, 2/11), without evidence of amyloidosis. C-reactive protein (81.8%, 9/11) and erythrocyte sedimentation (90.9%, 10/11) were increased during attacks. All patients harbored one to five different MEFV mutations, with E148Q and L110P being the most frequent. A novel non-synonymous mutation F636Y in exon 10 was discovered. Favorable responses to colchicine was observed in all six treated patients. Conclusion: The most common variants in our study were E148Q and L110P. F636Y may found for the first time. Colchicine led to favorable responses in all treated patients.